Kiss of the Night - Kenyon, Sherrilyn 1965- (New York : St. Martin's Paperbacks, 2004)
"Wulf is an ancient Viking warrior with a useful but extremely aggravating power: amnesia. No one who meets him in person can remember him 5 minutes later. It makes it easy to have one-night stands, but hard to have a meaningful relationship, and without true love he can never regain his soul. When he finally meets Cassandra, the one woman who can remember him, she turns out to be the princess of the cursed race he's sworn to hunt--and forbidden to him"--Amazon.com.
Keywords: Man-woman relationships -- Fiction; Vikings -- Fiction; Amnesia -- Fiction; Love stories; Fantasy fiction